The Influence of Natural Aging of the AW-2024 Aluminum Sheet on the Course of the Strain Hardening Curve - Stanisław Kut; Grzegorz Pasowicz (Advances in Mechanical and Materials Engineering)
Aluminum sheet drawpieces pressings with the ability to harden precipitation can be shaped from the sheet after annealing or heat treatment. In the second variant during the analysis and design of the technological proces, the change in the material properties of the shaped sheet due to natural aging should be additionaly taken into account. This article presents the results of research on the effect of the natural aging time after heat treatment of AW-2024 sheet material with a thickness of 1 mm on the course of the strain hardening curve. Strain hardening curves were determined on the basis of a uniaxial tensile test. The sheets were tested immediately after heat treatment and during natural aging, i.e. (20, 45, 90 and 120) minutes after heat treatment. The research showed a significant influence of natural aging in the tested range of times after heat treatment on the course of the deformation hardening curve of the sheet material. Based on experimentally determined in particular directions (0, 45 and 90 degrees to the rolling direction) the strain hardening curves, the values of material coefficients as a function of natural aging time were determined for four models of flow stress. Material coefficients in individual yield stress models were determined on the basis of approximation of strain hardening curves using the least squares method. On the basis of the analysis of approximation errors, the accuracy of the tested models of yield stress to describe the course of the hardening curve of the material of the tested sheet in the tested range of natural aging time was assessed.